To solve the equation \((-x) = -6\), the last step is to divide both sides by \(-1\). This gives:
\[ x = 6 \]
So, the correct option is:
B. Divide both sides by -1 to get x=6
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step?
options:
A. Use Property of Equality to get x= (-6)
B. Divide both sides by -1 to get x=6
C. Divide both sides by -1 to get x= (-6)
D. Use Multiplication Property of Equality to get x=6
1 answer
To solve the equation \((-x) = -6\), the last step is to divide both sides by \(-1\). This gives:
\[ x = 6 \]
So, the correct option is:
B. Divide both sides by -1 to get x=6